1999
DOI: 10.1017/s0021963098003448
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity

Abstract: We review recent research on the prevalence, causes, and effects of diagnostic comorbidity among the most common groups of child and adolescent psychiatric disorders; anxiety disorders, depressive disorders, attention deficit hyperactivity disorders, oppositional defiant and conduct disorders, and substance abuse. A meta-analysis of representative general population studies provides estimates of the strength of associations between pairs of disorders with narrower confidence intervals than have previously been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

48
732
8
40

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 596 publications
(828 citation statements)
references
References 0 publications
48
732
8
40
Order By: Relevance
“…Similar findings have been replicated by analyses of data from other large samples (Krueger and Markon 2006;Lahey et al 2004). Confirmatory factor analysis is appropriate to study adolescent psychopathology as pure psychiatric disorders are rare and clusters of disorders often co-occur at rates greater than chance (Angold et al 1999). …”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Similar findings have been replicated by analyses of data from other large samples (Krueger and Markon 2006;Lahey et al 2004). Confirmatory factor analysis is appropriate to study adolescent psychopathology as pure psychiatric disorders are rare and clusters of disorders often co-occur at rates greater than chance (Angold et al 1999). …”
mentioning
confidence: 61%
“…The first two-factor model (M2a) posits that the indicators for suicidality (SI and SA) load on one latent factor, that the indicators for psychopathology (MDE, PTSD, CD, AA, and DA) load on another latent factor, and that the latent factors are correlated. M2a has merit as there is evidence for comorbidity among psychiatric disorders (e.g., Angold et al 1999). The second two-factor model (M2b) suggests that the indicators for suicidality and internalizing (SI, SA, MDE, and PTSD) load on one latent factor, and it is related to an externalizing latent factor comprised of three indicators (CD, AA, and DA).…”
Section: Contributions Of the Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery that two or even more distinct psychiatric disorders jointly occur in one individual is very important, because psychiatric comorbidity often appears to connote greater impairment and chronicity [6]. Comorbidity often suggests poorer response to treatment and worse longitudinal trajectories [41].…”
Section: Introductionmentioning
confidence: 99%
“…Simonoff et al (2008) found that ß28% of school-aged children with ASD also fulfill DSM-IV criteria for ADHD and 9% for chronic tic disorder. A meta-analysis of ADHD yielded a 10.7-fold risk for conduct disorder, 5.5-fold for depression, and 3.0-fold for anxiety disorder (Angold et al, 1999).…”
mentioning
confidence: 99%